Molecular Subtyping of Invasive Breast Cancer Using a PAM50-Based Multigene Expression Test-Comparison with Molecular-Like Subtyping by Tumor Grade/Immunohistochemistry and Influence on Oncologist's Decision on Systemic Therapy in a Real-World Setting - Erber, Ramona; Angeloni, Miriam; Stöhr, Robert; Lux, Michael P.; Ulbrich-Gebauer, Daniel; Pelz, Enrico; Bankfalvi, Agnes; Schmid, Kurt W.; Walter, Robert F. H.; Vetter, Martina; Thomssen, Christoph; Mayr, Doris; et al. (International Journal of Molecular Sciences, 2022)
In intermediate risk hormone receptor (HR) positive, HER2 negative breast cancer (BC), the decision regarding adjuvant chemotherapy might be facilitated by multigene expression tests. In all, 142 intermediate risk BCs were investigated using the PAM50-based multigene expression test Prosigna (R) in a prospective multicentric study. In 119/142 cases, Prosigna (R) molecular subtyping was compared with local and two central (C1 and C6) molecular-like subtypes relying on both immunohistochemistry (IHC; HRs, HER2, Ki-67) and IHC + tumor grade (IHC+G) subtyping. According to local IHC, 35.4% were Luminal A-like and 64.6% Luminal B-like subtypes (local IHC+G subtype: 31.9% Luminal A-like; 68.1% Luminal B-like). In contrast to local and C1 subtyping, C6 classified >2/3 of cases as Luminal A-like. Pairwise agreement between Prosigna (R) subtyping and molecular-like subtypes was fair to moderate depending on molecular-like subtyping method and center. The best agreement was observed between Prosigna (R) (53.8% Luminal A; 44.5% Luminal B) and C1 surrogate subtyping (Cohen's kappa = 0.455). Adjuvant chemotherapy was suggested to 44.2% and 88.6% of Prosigna (R) Luminal A and Luminal B cases, respectively. Out of all Luminal A-like cases (locally IHC/IHC+G subtyping), adjuvant chemotherapy was recommended if Prosigna (R) testing classified as Prosigna (R) Luminal A at high / intermediate risk or upgraded to Prosigna (R) Luminal B.
CRIS-Team WoS Importer:2022-08-26